2014
DOI: 10.1080/17461391.2014.971879
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics supplementation for athletes – Clinical and physiological effects

Abstract: Probiotic supplementation has traditionally focused on gut health. However, in recent years, the clinical applications of probiotics have broadened to allergic, metabolic, inflammatory, gastrointestinal and respiratory conditions. Gastrointestinal health is important for regulating adaptation to exercise and physical activity. Symptoms such as nausea, bloating, cramping, pain, diarrhoea and bleeding occur in some athletes, particularly during prolonged exhaustive events. Several studies conducted since 2006 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 63 publications
2
124
0
9
Order By: Relevance
“…Human runners with supplementation of multi-strain probiotics demonstrated increased run time to fatigue in heat [32]. In other practices, probiotics is found to modulate exercise performance through multiple mechanisms, including inflammation, oxidative stress and gut-intestinal integrity [33][34][35][36]. Collectively, these results argued the tight relationship between gut microbiota changes and the physical exercise performance (Fig.…”
Section: Introductionmentioning
confidence: 78%
“…Human runners with supplementation of multi-strain probiotics demonstrated increased run time to fatigue in heat [32]. In other practices, probiotics is found to modulate exercise performance through multiple mechanisms, including inflammation, oxidative stress and gut-intestinal integrity [33][34][35][36]. Collectively, these results argued the tight relationship between gut microbiota changes and the physical exercise performance (Fig.…”
Section: Introductionmentioning
confidence: 78%
“…A meta-analysis using data from both athlete and non-athlete studies concluded that there is a likely benefit of reducing URTI incidence [45]. The likely mechanisms of action for probiotics include direct interaction with the gut microbiota, interaction with the mucosal immune system and immune signaling to a variety of organs and systems [46]. A recent report by He and colleagues noted gender differences in the number and duration of respiratory-tract illness symptoms in endurance athletes during a winter training period indicating that females may be more susceptible to URTI than their male counterparts [5].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the immunomodulatory effects are likely strain-specific [4]. The purported anti-inflammatory effects of probiotics have received considerable attention in the athletic community [5]. However, despite that attention, few studies have examined the effect of probiotics in an athletic population.…”
Section: Introductionmentioning
confidence: 99%